IMPLEMENTASI MANAJEMEN BANDWIDTH MENGGUNAKAN QUEUE TREE ROUTER MIKROTIK - Iin Marlina; Andreas Perdana (LPPM Universitas Muhammadiyah Kotabumi, 2022)
The development of information technology is currently developing very quickly, both software and hardware, in line with the needs of modern humans. The internet is one of the information technologies that has had a tremendous impact on many aspects of human life. with equipment and software for bandwidth management, computer networks can function properly. The world of education, government and private agencies, and all jobs in general require bandwidth management with Mikrotik routers to help overcome traffic congestion that can disrupt computer network connections. because computer networks can go down or have problems because there is no equal distribution of bandwidth for each user, therefore it is necessary to make large bandwidth distribution arrangements, with the aim of achieving optimal bandwidth capacity for each user. Other factors can also affect network throughput, such as packet loss, certain network protocols, and device networks. Queue trees can provide limits for specific IP addresses, subnets, protocols, ports, and other parameters. Queue trees limit peer-to-pee traffic. Prioritize some flow packets over others. Queue tree can be configured for download and upload traffic so web browsing can be faster. Apply different limits based on time. And share available traffic among users equally or depending on channel load. Function per queue connection. PCQ is one of the functions used for bandwidth management to improve system performance.